Higher cardiovascular mortality in men with persistent dipstick hematuria - Iseki, Kunitoshi; Konta, Tsuneo; Asahi, Koichi; Yamagata, Kunihiro; Fujimoto, Shouichi; Tsuruya, Kazuhiko; Narita, Ichiei; Kasahara, Masato; Shibagaki, Yugo; Moriyama, Toshiki; Kondo, Masahide; Watanabe, Tsuyoshi (Clinical and experimental nephrology, 2021)
Background We previously reported that dipstick hematuria (UH) was associated with higher all-cause mortality in men, but not in women. We extended the observation and examined the causes of death using repeated urinalysis in men. Methods Subjects were those who participated the Tokutei–Kenshin between 2008 to 2015 in seven districts. Using National database of death certificate, we identified those who might have died and confirmed further with the collaborations of the regional National Health Insurance agency and public health nurses. Dipstick results of 1 + and higher were defined as hematuria. Hazard ratio (HR) and 95% confidence interval (CI) were calculated using the Cox proportional hazard analysis. We adjusted for age, body mass index, eGFR, proteinuria, comorbid condition (diabetes mellitus, hypertension, and dyslipidemia), past history (stroke, heart disease, and kidney disease), and lifestyle (smoking, drinking, walking, and exercise). Results A total of 170,119 men were studied and 70,350 (41.4% of the total) were re-examined next year. The prevalence of UH (−/−), UH (−/+), UH (±), and UH (+ /+) was 77.2% ( N = 54,298), 14.0% ( N = 9,838), 1.4% ( N = 1014) and 7.4% ( N = 5,200), respectively. We identified 1,162 deaths (1.7% of the total of the re-examined). The adjusted HR (95% CI) was 1.49 (1.22–1.81) for all-cause mortality and 1.83 (1.23–2.71) for cardiovascular death compared to those with UH (−/−), respectively. However, that for cancer mortality risk was not significant: 1.23 (0.92–1.64). Conclusions In men, persistent dipstick hematuria is a significantly risk factor of all-cause mortality, in particular cardiovascular death among general screening participants.